2018
DOI: 10.1080/08927014.2018.1464152
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of biofilm formation on biocidal antifouling and fouling-release coatings using next-generation DNA sequencing

Abstract: The bacterial and eukaryotic communities forming biofilms on six different antifouling coatings, three biocidal and three fouling-release, on boards statically submerged in a marine environment were studied using next-generation sequencing. Sequenced amplicons of bacterial 16S ribosomal DNA and eukaryotic ribosomal DNA internal transcribed spacer were assigned taxonomy by comparison to reference databases and relative abundances were calculated. Differences in species composition, bacterial and eukaryotic, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…In this study we employed a non-fouling release paint, and the dominant taxa were Alphaproteobacteria, Gammaproteobacteria, Firmicutes, and Bacteroidetes, similar to previous studies describing marine biofilm communities in fouling-release biocide-based coatings (McNamara et al, 2009;Chen et al, 2013). Fouling-release coatings revealed a significant effect on the phylum Proteobacteria and Bacteroidetes growth (Winfield et al, 2018), and another study demonstrated a sensitivity of Bacteroidetes and Actinobacteria to coatings based on pyrithione (Briand et al, 2017). In our study, however these most abundant phyla were not influenced by the applied anti-corrosion Intersheen 579 paint.…”
Section: Taxonomy Of Biofilms On Plates With Anti-corrosion Paint Andmentioning
confidence: 61%
See 1 more Smart Citation
“…In this study we employed a non-fouling release paint, and the dominant taxa were Alphaproteobacteria, Gammaproteobacteria, Firmicutes, and Bacteroidetes, similar to previous studies describing marine biofilm communities in fouling-release biocide-based coatings (McNamara et al, 2009;Chen et al, 2013). Fouling-release coatings revealed a significant effect on the phylum Proteobacteria and Bacteroidetes growth (Winfield et al, 2018), and another study demonstrated a sensitivity of Bacteroidetes and Actinobacteria to coatings based on pyrithione (Briand et al, 2017). In our study, however these most abundant phyla were not influenced by the applied anti-corrosion Intersheen 579 paint.…”
Section: Taxonomy Of Biofilms On Plates With Anti-corrosion Paint Andmentioning
confidence: 61%
“…In our results however, we found a strong dominance of the motile pennate diatom Haslea sp. (over 80%) in the last day spring sampling (Figure 6), a genus which is known to colonize artificial surfaces (Winfield et al, 2018), while it had a much lower presence during winter (lower than 5%). The higher abundance of these phototrophic microorganisms could be explained by the significantly longer daylength during spring (see Table 1).…”
Section: Detection Of Possible Pathogenic Species and Identification mentioning
confidence: 99%
“…Biocidal antifouling coatings function through the release of certain toxic chemicals (biocides) to deter the settlement and growth of organisms. Biocidal coatings remain the most popular choice and still dominate the market reportedly accounting for more than 90% of coatings sales (Lejars et al ., 2012; Winfield et al ., 2018), although concerns over the potential environmental impact of biocides have led to increased attention being paid to the development of biocide-free approaches to fouling control (Lejars et al ., 2012). Non-biocidal fouling-release coatings function based on a low surface energy, smooth and non-porous, free of reactive functional groups (Finnie & Williams 2010) which reduces an organism’s ability to generate a strong interfacial bond with the surface (Chambers et al ., 2006; Lejars et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a handful of studies have reported the application of next generation sequencing (NGS) techniques to investigate the response of marine biofilm community profiles developed on marine fouling control coatings (Muthukrishnan et al ., 2014; Leary et al ., 2014; Briand et al ., 2017; Flach et al ., 2017; Hunsucker et al ., 2018; Winfield et al ., 2018; von Ammon et al ., 2018; Dobretsov et al ., 2019; Ding et al ., 2019). NGS technology based on sequencing ribosomal RNA genes, is appropriate for a range of applications including highly diverse community analysis, while offering large volume of data that allow for statistical testing (Fukuda et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation